1965
DOI: 10.1002/pssb.19650090114
|View full text |Cite
|
Sign up to set email alerts
|

A Model of “Lattice” Hardening in Irradiated Copper Crystals with the External Characteristics of “Source” Hardening

Abstract: A model is proposed to explain the formation of slip lines in irradiated copper crystals during the propagation of the Lüders front. In this model it is shown that, due to the sweeping up of the irradiation produced defect clusters by deformation, the critical stress to produce a slip line is that required to operate the source in producing the first dislocation loop in the environment of the defect clusters. As the slipped area expands a pile‐up forms and the stress required to expand this pile‐up falls. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 12 publications
5
35
0
Order By: Relevance
“…Early studies of radiation hardening produced competing models for the hardening mechanism, based on either dislocation source locking or lattice friction. Several researchers have proposed that both mechanisms operate, with source hardening responsible for the upper yield point and lattice hardening responsible for the lower yield stress observed in metals irradiated at low temperatures [19,20]. The loss of work hardening capacity produces sharp decreases in uniform elongation.…”
Section: Resultsmentioning
confidence: 98%
“…Early studies of radiation hardening produced competing models for the hardening mechanism, based on either dislocation source locking or lattice friction. Several researchers have proposed that both mechanisms operate, with source hardening responsible for the upper yield point and lattice hardening responsible for the lower yield stress observed in metals irradiated at low temperatures [19,20]. The loss of work hardening capacity produces sharp decreases in uniform elongation.…”
Section: Resultsmentioning
confidence: 98%
“…It is also well known that the velocity of glide dislocations increases exponentially with stress [25], which invokes high strain rates in channels. Indeed, high speed photography of the surface slip lines resulting from DCD has shown that they develop very rapidly, in less than a millisecond [28,29]. Details of the barrier clearing process(es) are specific to particular types of barriers and are still very much debatable.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that the velocity of glide dislocations increases exponentially with stress [31], which invokes high strain rates in channels. Indeed, high speed photography of the surface slip lines resulting from DCD has shown that they develop very rapidly, in less than a millisecond [18,35]. Details of the barrier clearing process(es) are specific to particular types of barriers and are still very much debatable.…”
Section: Dislocation Channeling and Tensile Curve Behaviormentioning
confidence: 98%